COMPOUND ODONTOMA IN CHILDHOOD POPULATION (CASE REPORT) - Janev, Edvard Jordan; Redzep, Enis; Kanurkova, Lidija; Tosevska, Simona (Journal of Morphological Sciences; Vol 3 No 1 (2020): JMS, 2020)
Odontomas are odontogenic benign tumors composed of dental tissue. Most of these lesions are asymptomatic and are often detected on routine radiographs. Morphologically odontomas can be classified as complex, when present as irregular masses containing different types of dental tissues, or as compound if there is superficial anatomic similarity to even rudimentary teeth â€“ the denticles. They are considered to be hamartomas rather than neoplasms, and are composed of natural teeth tissues: enamel, dentin, cementum and pulp tissue.The aim of this study is to show the significance of persistence for these asymptomatic malformations which usually can lead to malocclusion or many different orthodontic irregularities. A 13-year-old girl with mixed dentition attended our Dental Clinic appointment with doubt about the apparent delay in exfoliation of deciduous teeth: 63â€“64. A panoramic radiograph showed retained left maxillary canine and first premolar. While the presence of undefined lesion formed by many radiopaque small tooth-like structures constituting an obstacle to the respective permanent teeth eruption. Under local anesthesia, access to the lesion was achieved via intra-oral approach and its surgical removal was performed. The histopathologic examination confirmed the diagnosis of compound odontoma. Routine radiographic examination is important for early detection of silent lesions such as odontomas.  Key words: odontogenic tumors, diagnosis, odontoma, lesion.